2012
DOI: 10.1021/nl301690e
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Synthesis of AlN/GaN Multiple Quantum Well Nanowire Structures and Their Optical Properties

Abstract: We report the controlled synthesis of AlN/GaN multi-quantum well (MQW) radial nanowire heterostructures by metal-organic chemical vapor deposition. The structure consists of a single-crystal GaN nanowire core and an epitaxially grown (AlN/GaN)(m) (m = 3, 13) MQW shell. Optical excitation of individual MQW nanowires yielded strong, blue-shifted photoluminescence in the range 340-360 nm, with respect to the GaN near band-edge emission at 368.8 nm. Cathodoluminescence analysis on the cross-sectional MQW nanowire … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 53 publications
1
35
1
Order By: Relevance
“…[1][2][3] UV-LEDs are targeted for a wide range of potential applications, such as water purification, sterilization, biological detection, medical treatment, and high-density optical recording. [4][5][6] For these devices, hexagonal AlGaN is one of the most suitable materials because its Al content-dependent energy band gap lies within the range of 3.4 -6.2 eV at 300 K. Unfortunately, due to the low surface migration rate of Al atoms and the strong parasitic reaction inside AlGaN epilayers grown by metal organic chemical vapor deposition (MOCVD), adduct compounds are usually generated; these tend to be converted into solid particles of Al and Ga, resulting in poor crystal quality.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] UV-LEDs are targeted for a wide range of potential applications, such as water purification, sterilization, biological detection, medical treatment, and high-density optical recording. [4][5][6] For these devices, hexagonal AlGaN is one of the most suitable materials because its Al content-dependent energy band gap lies within the range of 3.4 -6.2 eV at 300 K. Unfortunately, due to the low surface migration rate of Al atoms and the strong parasitic reaction inside AlGaN epilayers grown by metal organic chemical vapor deposition (MOCVD), adduct compounds are usually generated; these tend to be converted into solid particles of Al and Ga, resulting in poor crystal quality.…”
Section: Introductionmentioning
confidence: 99%
“…More crystalline property studies were shown in TEM data. Visibly only the middle part of both the nanowires which is m-plane, reveals better crystalline properties compared to top and bottom part because this area is mostly free of defects and strain as defects and strain are concentrated at the edges or corners of c and r-plane of nanowires3536. Interestingly the top area CL emission of hollow nanowire shows a redshift to higher wavelength which is again demonstrated in PL data.…”
Section: Resultsmentioning
confidence: 58%
“…Large bandgap, intense optical activity, and electronic confinement make the GaN nanoparticles highly attractive for use in applications, including the fabrication of highly efficient nanophotonic devices , nanosensors , and photocatalysts . Additionally, the basic development of science related to the growth and physical properties of this type of nanoparticle is a rapidly growing field.…”
Section: Introductionmentioning
confidence: 99%